DAMPAK PENGGUNAAN MEDIA SOSIAL TERHADAP AKHLAK PADA ANAK USIA SEKOLAH DASAR - Munawar, Mohamad (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2024)
The impact of social media will always be positive and negative, it depends on the user and each of us, whether we can take advantage of it or can only get caught up in things that are negative. Good morals will be formed from an early age, including in the teenage phase, which is very important for the future of the teenager himself. The influence of social media on teenagers today also has an impact on the morals or character of teenagers, because of the nature of social media which makes its users addicted, and social media does not have patent rules, in terms of the language used or words that are actually inappropriate. to say or not to say on social media. This makes today's teenagers less ethical towards fellow students and even less ethical towards their parents. Several inappropriate photos uploaded or exhibited on social media have now become a trend among teenagers. Guidance becomes spectacle and spectacle becomes guidance, this is how teenagers behave today. The lack of knowledge regarding religious knowledge, especially regarding the morals of teenagers, means that they do not understand and understand the importance of morals for themselves, so that they seem to have no ethics when commenting or writing statuses on social media at will without thinking about whether what they write deviates from what religion teaches. Keywords: Social Media, Adolescent Morals